Pattern recognition and machine intelligence 4th International Conference, PReMI 2011, Moscow, Russia, June 27 - July 1, 2011 : proceedings - Kuznetsov, Sergei O. (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Pattern Recognition and Machine Intelligence, PReMI 2011, held in Moscow, Russia in June/July 2011. The 65 revised papers presented together with 5 invited talks were carefully reviewed and selected from 140 submissions. The papers are organized in topical sections on pattern recognition and machine learning; image analysis; image and video information retrieval; natural language processing and text and data mining; watermarking, steganography and biometrics; soft computing and applications; clustering and network analysis; bio and chemo analysis; and document image processing.